2016
DOI: 10.1002/nbm.3539
|View full text |Cite
|
Sign up to set email alerts
|

Brain γ-aminobutyric acid (GABA) detectionin vivowith theJ-editing1H MRS technique: a comprehensive methodological evaluation of sensitivity enhancement, macromolecule contamination and test-retest reliability

Abstract: Abnormalities in brain γ-aminobutyric acid (GABA) have been implicated in various neuropsychiatric and neurological disorders. However, in vivo GABA detection by proton magnetic resonance spectroscopy (1H MRS) presents significant challenges arising from low brain concentration, overlap by much stronger resonances, and contamination by mobile macromolecule (MM) signals. This study addresses these impediments to reliable brain GABA detection with the J-editing difference technique on a 3T MR system in healthy h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 41 publications
4
88
1
Order By: Relevance
“…The ratio between MM-suppressed GABA and GABA+ measurements (0.38) is lower than expected. Typically, it is assumed that ~50% of the GABA+ signal is GABA (Harris et al, 2015a; Mikkelsen et al, 2016a; Shungu et al, 2016). This is largely explained by differential T 2 relaxation between GABA signal at TE = 68 ms and TE = 80 ms (13% edited signal loss based on a T 2 of 88 ms (Edden et al, 2012b)) and artificially reduced “MM-suppressed GABA” values due to negative MM co-editing (~5% edited signal loss due to mean truenormalΔδ0¯ of −0.005 ppm (see Edden et al, 2016)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio between MM-suppressed GABA and GABA+ measurements (0.38) is lower than expected. Typically, it is assumed that ~50% of the GABA+ signal is GABA (Harris et al, 2015a; Mikkelsen et al, 2016a; Shungu et al, 2016). This is largely explained by differential T 2 relaxation between GABA signal at TE = 68 ms and TE = 80 ms (13% edited signal loss based on a T 2 of 88 ms (Edden et al, 2012b)) and artificially reduced “MM-suppressed GABA” values due to negative MM co-editing (~5% edited signal loss due to mean truenormalΔδ0¯ of −0.005 ppm (see Edden et al, 2016)).…”
Section: Discussionmentioning
confidence: 99%
“…Difference editing techniques in particular use frequency-selective inversion pulses to achieve this (for methodological reviews, see Harris et al, 2017; Puts and Edden, 2012). The popularity of MEGA-PRESS is attributed to a number of factors, including the wide availability of the basic PRESS sequence across scanner platforms, its relatively straightforward implementation (Mullins et al, 2014), its reproducibility (Bogner et al, 2010; Brix et al, 2017; Geramita et al, 2011; Mikkelsen et al, 2016a; Near et al, 2014; O’Gorman et al, 2011; Shungu et al, 2016) and continued development of acquisition methodology and data processing tools (Chan et al, 2016; Edden et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…First, conventional short echo time (TE) spectra were obtained using the Stimulated Echo Acquisition Mode (STEAM) sequence with repetition time (TR) = 5000 ms, echo time (TE) = 15 ms and 48 signal averages to record spectra from a 1.5×2.0×2.0-cm 3 voxel prescribed in the ACC and in the left cerebellum (Fig 1). Next, without moving the subjects spectra were again obtained from a 3x3x3-cm 3 voxel, but using the standard Point RESolved Spectroscopy (PRESS) sequence, which had been modified to enable the detection of γ-aminobutyric acid (GABA) by J-edited spin echo difference technique [16], as fully described recently [17,18]. Briefly, to implement the J-editing technique, a pair of a frequency-selective inversion pulses was inserted into the standard PRESS method, and then applied on the GABA C-3 resonance at 1.9 ppm on alternate scans, using TE/TR 68/2500ms.…”
Section: Methodsmentioning
confidence: 99%
“…Finally measurement reproducibility will influence these results but is not accounted for in the κ,μ-correction. Most recently, Shungu et al [42] showed excellent test-retest GABA repeatability for both water-referenced and Cr-referenced data. In the literature, reproducibility of measurements is variable with test-retest studies presenting CVs from as low as 5%, as per Shungu et al, intermediate values of 8–15% as seen by Evans et al [14] and O’Gorman et al [43], to larger values 13–20%, as seen by Bogner et al [35].…”
Section: Discussionmentioning
confidence: 99%